Psychiatric disorder or impairing psychology in children who have been excluded from school: A systematic review. (October 2014) - Whear, Rebecca; Marlow, Ruth; Boddy, Kate; Ukoumunne, Obioha C.; Parker, Claire; Ford, Tamsin; Thompson-Coon, Jo; Stein, Ken
When children with special educational needs are excluded from school, it should raise the concern that these children are not receiving adequate help and support. This systematic review aims to identify the prevalence of psychiatric disorder or impairing psychopathology among children who are excluded from school compared to children who are not excluded from school. The review follows the guidelines set out by the Centre of Research and Dissemination (Centre for Reviews and Dissemination, 2009 ). We used broad search terms (across 16 databases) in order to avoid missing papers, our initial screening stage involved 3712 titles and abstracts. Five studies finally met our inclusion criteria. The results from these studies suggest that the odds of children who have been excluded from school having some kind of impairing psychological or behavioural impairment is increased in comparison to children who have not been excluded (odds ratios ranging from 1.13–31.9). However, the paucity of primary research in this area, combined with methodological weaknesses in the identified studies makes it difficult to draw firm conclusions. The need for education and mental health professionals to work together to provide the appropriate support for all children at risk of exclusion is of great and immediate concern.